The Use of CT Scan in Hemodynamically Stable Children with Blunt Abdominal Trauma: Look before You Leap - Nellensteijn, David R.; Greuter, Marcel J.; el Moumni, Moustafa; Hulscher, Jan B. (European Journal of Pediatric Surgery, 2016)
We set out to determine the diagnostic value of computed tomographic (CT) scans in relation to the radiation dose, tumor incidence, and tumor mortality by radiation for hemodynamically stable pediatric patients with blunt abdominal injury. We focused on the changes in management because of new information obtained by CT. CT scans for suspected pediatric abdominal injury performed in our accident and emergency department were retrieved from the radiology registry and analyzed for: injury and hemodynamic parameters, changes in therapy, and radiological interventions. The dose length product (DLP) was used to calculate the effective dose (ED) and with the BEIR VII report we calculated the estimated induced lifetime tumor and mortality risk. Seventy-two patients underwent abdominal CT scanning for suspicion of abdominal injury and eight patients were excluded for hemodynamic instability, leaving 64 hemodynamically stable patients. Four patients died (6%). On the remaining 60 patients, only one laparotomy was performed for suspicion of duodenal perforation. Only in three out of the 64 hemodynamically stable cases (5%), a CT scan brought forward an indication for intervention or change in management. One patient was suspected of a duodenal perforation and underwent a laparotomy. A grade II hepatic laceration, but no duodenal, injury was found. Two patients underwent embolization of the splenic artery. One for an arterial blush caused by splenic laceration as was observed on the contrast enhanced-CT. Patient remained stable and during the angiogram the blush had disappeared. The second patient underwent (prophylactic) selective arterial embolization for having sustained a grade V splenic injury. The median radiation dosage was 11.43 mSv (range 1.19–23.76 mSv) in our patients. The use of the BEIR VII methodology results in an estimated increase in the lifetime tumor incidence of 0.17% (range, 0.05–0.67%) and an estimated increase in lifetime tumor incidence of 0.08% (0.02–0.28%). The results of our data suggest that the use of CT scans can largely be avoided in hemodynamically stable children with blunt abdominal injury.
Keywords: abdominal injury; CT scan; radiation dose